Examining the fluidity of innovation teams: a conceptual framework - Linhardt, Rylee M.; Salas, Eduardo (Frontiers in Psychology, 2023)
As innovative endeavors have become more complex and time-intensive, there has become an increasing reliance on expert teams in organizations. Expert innovation teams are comprised of team members with extensive experience and mastery in a particular discipline. These teams utilize fluid membership that expands the available knowledge of the team but creates challenges for effective teamwork. We argue that the mechanism for creating an enduring impact and developing a product to fruition requires the cognitive and social integration of fluid team members. This article focuses on how teams effectively integrate knowledge with diverse, and possibly fluid, team members and how teams can organize knowledge through planning and reflection to implement the idea successfully. Knowledge integration and team reflexivity are considered in tandem to emphasize the multi-faceted nature of generating and implementing innovative solutions and the conflicting teamwork processes that hinder innovative efforts. To understand how these competing teamwork processes required for successful innovation interact, we developed a framework that considers resilience as the factor that elicits team creative performance. In doing so, we discuss how innovation teams build resilience over time and how creative failure can lead to greater levels of innovation.